An increase in the blood thyroxine level after methylene blue in rats: the interaction with carbimazole - Nedvídková, J; Sterzl, I; Haluzík, M; Schreiber, V (Endocrine research, 1995)
Anterior pituitary (AP) weight, thyroid weight, the serum thyroxine (T4) level, the thyroid T4 and cAMP content, the serum TSH level and the TSH and cAMP content of the AP and thyroid were measured in control rats, rats given methylene blue (MB) in their food, rats given the thyroid-blocking agent carbimazole (CARB) and rats fed both MB and CARB. AP weight fell slightly after MB in both intact and CARB--fed animals. Thyroid weight rose strongly after CARB, MB partly inhibited this increase. The cAMP content of the thyroid rose after CARB; this increase was likewise blocked by MB, MB alone had no effect on the thyroid cAMP concentration. Previous observations showing that MB produced an increase in the blood T, were confirmed. The T4 level fell, of course, after CARB and the decrease was partly inhibited by MB. The T4 content of the thyroid also fell after CARB, this decrease was completely reversed by MB. The blood TSH level fell slightly after MB and rose 7--fold after a CARB blockade of the thyroid; this increase was completely inhibited by MB. The TSH content of the AP fell after MB in both intact and CARB--fed animals. The cAMP content of the AP fell after MB, it was unaffected by CARB. Thus, in some way, MB raised the blood thyroxine level in both intact and CARB--fed animals and strongly depressed the TSH content in the serum and the AP given alone or with CARB. The mechanism of this action should be a result of MB interaction in thyroid hormone metabolism and their binding activity on specific regulatory elements. It is a problem for future experiments.
Keywords: radioimunoanalýza; thyroxin; karbimazol; Rats; Radioimmunoassay; Pituitary Gland, Anterior; Antithyroid Agents; AMP cyklický; Rats, Wistar; mužské pohlaví; aplikace orální; Methylene Blue; Thyroid Gland; Carbimazole; krysa rodu Rattus; Cyclic AMP; Thyrotropin; thyreotropin; Organ Size; velikost orgánu; antidota; zvířata; štítná žláza; Administration, Oral; thyreostatika; Antidotes; potkani Wistar; Thyroxine; methylenová modř; Male; adenohypofýza; Animals